Acute Kidney Injury During Pregnancy and Puerperium - Iram Taj, Bakhtawar, Kaneez Zehra Naqvi, Nazia Mushtaq, Adilatahir, Hafiza Yasmeen Abbas, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Acute kidney injury (AKI) is a serious complication in perilous patients substantially related to long-term chronic kidney disease (CKD) with increased morbidity, hospital duration, and mortality. AKI during pregnancy is a life-threatening disease related to maternal and fetal loss contributing to 30% to 60% of mortality. Though a rare cases of AKI during pregnancy has been reported in previous studies. But the present study aimed to assess the acute kidney injury during pregnancy and puerperium. Methodology: This cross-sectional study was conducted on 205 pregnant or puerperium women with acute kidney injury or acute renal failure in the Department of Gynaecology and Obstetrics and Nephrology, Liaquat National Hospital, Karachi from January 2019 to December 2021. All the pregnant women of age 22 to 40 years with no prior co-morbidities were enrolled in this study. Patients with history of autoimmune disease, chronic kidney disease before pregnancy, higher level of serum creatinine, hypertension before gestation and renal stone diseases, renal scarring on ultrasonography or small size of the kidneys were all excluded. An informed consent was taken from all the patients. Patient’s detailed history, laboratory investigations, demographic details, and clinical presentation were recorded. Laboratory examination involve CBC and renal function tests. Each patient had a thorough obstetric examination. Hemodialysis was performed as per standard indications. Acute kidney injury was assessed. SPSS version 25 was used for data analysis. Results: The incidence of acute kidney injury in pregnant and puerperium women was 21.5% (n=44). The overall mean age was 31.42 ± 4.35 years. Mean parity was 3.2. During pregnancy, the most prevalent cause of acute kidney injury was pre-eclampsia with incidence rate of 28 (63.6%) followed by postpartum hemorrhage in 8 (18.2%). About 6 (13.6%) patients had regain renal function and discharged from the hospital. Maternal mortality was found in 2 (4.5%) cases. Of the remaining 161 pregnant women without AKI cases, the prevalence of postpartum hemorrhage, HELLP syndrome, pre-eclampsia/eclampsia, and pregnant fatty liver were 58 (36.02%), 17 (10.6%), 66 (41%), and 20 (12.4%) respectively. Apart from hemorrhagic shock and amniotic fluid embolism, maternal outcomes was good. No significant association was found between acute kidney injury and outcomes with 5% level of significance. Conclusion: The present study found a higher prevalence of acute kidney injury in pregnant women. Pre-eclampsia and postpartum hemorrhage was the prevalent causes for AKI in pregnant women. Postpartum hemorrhage and amniotic fluid embolism were the major causes for mortality of pregnant women with AKI. The mortality of pregnant women with AKI is mostly caused by postpartum hemorrhage and pre-eclampsia. Poor outcome might be predicted by renal therapy need in acute kidney injury. Further studies is required to be conducted in order to improve pregnancy associated AKI outcomes. Keywords: Acute kidney Injury, Pregnant women, Puerperium